The Effectiveness of Online Learning System in Arabic Subject at Al-Ulum Islamic Junior High School Integrated of Medan - Setiawan, Hasrian Rudi; Ritonga, Mahyudin (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study is to find out whether the bold learning system is effective in Arabic subjects at Al-Ulum Islamic Junior High School Integrated of Medan. In addition, this research also aimed to evaluate the quality of the online learning system that had been carried out. The method that was used in this research was a descriptive quantitative method with survey techniques. This research used a sample of 290 students. In this research, the data was taken by using Likert Scale survey method. Data analysis in this study, namely by calculating the presentation of data on each indicator of online learning activities. The results of the research showed that the effectiveness of online learning in Arabic subject at Al-Ulum Islamic Junior High School Integrated of Medan reached 72 %, or that was in a good category. This illustrates that the online learning system for Arabic subjects is implemented at Al-Ulum Islamic Junior High School Integrated of Medan running effectively. However, teachers and school administrators need to evaluate and then make gradual improvements so that the effectiveness of online learning, especially in Arabic subjects, can be further improved.